1968
DOI: 10.1139/y68-124
|View full text |Cite
|
Sign up to set email alerts
|

Active state prolongation associated with depolarization in frog's skeletal muscle

Abstract: If the K+ content of normal Ringer solution is increased, the duration of the plateau of the active state begins to rise at 8–10 mM [K]out. If the Cl− of the Ringer solution is replaced by NO3−, the active state duration begins to rise at 4–5 mM [K]out, and increases markedly with further depolarization. The observed dependence of active state duration on [K]out is similar to the known relation between resting metabolism and [K]out and is taken as evidence in support of the concept of subthreshold activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Maintained, subthreshold depolarization of a muscle is known to be associated with a prolongation of the active state. This effect was not related to an increase in the action potential "area" (Clinch 1968). In several previous studies, hypertonic solutions were reported to cause a depolarization of the muscle (Tigyi andShih-Fang 1962, Gordon andGodt 1970), but the measurements were usually performed in solutions of very high tonicity, 3-4 R. The present experiments did not show any marked changes of the membrane potential in 1.44-1.67 R. In some fibres there was a slight depolarization, but more often a hyperpolarization of 3-8 mV was seen.…”
Section: Discussionmentioning
confidence: 74%
“…Maintained, subthreshold depolarization of a muscle is known to be associated with a prolongation of the active state. This effect was not related to an increase in the action potential "area" (Clinch 1968). In several previous studies, hypertonic solutions were reported to cause a depolarization of the muscle (Tigyi andShih-Fang 1962, Gordon andGodt 1970), but the measurements were usually performed in solutions of very high tonicity, 3-4 R. The present experiments did not show any marked changes of the membrane potential in 1.44-1.67 R. In some fibres there was a slight depolarization, but more often a hyperpolarization of 3-8 mV was seen.…”
Section: Discussionmentioning
confidence: 74%
“…From the argument offered above regarding the total absence of the positive inotropic effect when the potassium level is raised only in the long segment, it may be regarded as unlikely that membrane depolarization during the resting state (i.e., diastole) is involved in the mechanism of the positive inotropic effect. This is in contrast to the effect of potassium-induced depolarization in prolonging the active state in skeletal muscle (Clinch, 1968;Chapman, 1969). Additional evidence on this point has been provided by Beeler and Reuter (1970 b), who found that small depolarizations (e.g., 8 my, as in Fig.…”
Section: Discussionmentioning
confidence: 78%